Los Angeles Dodgers 5 vs Atlanta Braves 2 at Dodger Stadium - Watkins, Howard::::::::: (1987)
Dodger #3 Steve Sax steals second base as he beats tag by Atlanta Braves shortstop #14 Viewed from centerfield